Ozone spectroscopy in the electronic ground state: High-resolution spectra analyses and update of line parameters since 2003 - Barbe A.; Mikhailenko S. N. Semen Nikolaevich; Starikova E.; Backer M.- R. De; Tyuterev Vl. G.; Mondelain D.; Kassi S.; Campargue A.; Janssen C.; Tashkun S.; Kochanov R. (2013, 2013)
Title screen